KNOWLEDGE, ATTITUDE, AND PRACTICES TOWARDS MENSTRUAL HYGIENE AMONG FEMALE STUDENTS AGED 18 TO 35 YEARS IN KAMPALA SCHOOL OF HEALTH SCIENCES BULOBA CAMPUS, WAKISO DISTRICT. A CROSS-SECTIONAL STUDY. - SHERINA TWAFUNA; Alex Katwe (Student's Journal of Health Research, 2023)
Introduction: Specific objectives of the study were To determine the level of knowledge, attitude, and practices of menstrual hygiene, among female students aged 18 to 35 years in Kampala School of Health sciences Buloba campus Wakiso district. Methodology: A descriptive cross-sectional study was carried out with a simple random sampling technique to select participants whereas data was collected using a self-administered questionnaire developed by the researcher. The analysis of the data collected was done manually using tally sheets and data was systematically computed into frequency and percentage using findings to generate tables and figures for easy presentation., Results: 50 participants out of 50 invited participants fully completed the study. Participants had good knowledge where teachers were the first informants in 80% of the females, 80% correctly defined menstruation, and 94% considered disposable sanitary pads the ideal menstrual absorbent. They had averagely good attitudes where 60% reported that they felt scared at first menarche, 40% perceived menstruation as unclean or embarrassing, and 86% of the females reported never encountering secondary stigma as a result of menstruation. They also had good practices towards menstrual hygiene 54% of the females changed their sanitary material two times a day and 34% changed thrice, 74% of females took a bath twice during their period with 94% using water and soap. Conclusion: Attitude toward menstrual hygiene among females is still challenging followed by practices and yet knowledge is generally good. Recommendations: There is a need to create awareness of healthy menstrual practices, impart reproductive health education including menstrual hygiene, to acquire skills usually through training or workshops, and matters concerning menstrual hygiene should be discussed with female students and solutions sought to improvise on disposal bins and incinerators.